2021
DOI: 10.3390/w13111515
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Shallow Urban Groundwater at Regional and Local Scales: A Case Study in Detroit, MI

Abstract: Groundwater plays a significant role in the vitality of the Great Lakes Basin, supplying water for various sections. Due to the interconnection of groundwater and surface water features in this region, the groundwater quality can be affected, leading to potential economic, political, health, and social issues for the region. Groundwater resources have received less emphasis, perhaps due to an “out of sight, out of mind” mentality. The incomplete characterization of groundwater, especially shallow, near-surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Teimoori et al (2021) found that the modeled depth to groundwater in Detroit ranged from approximately 1-3 meters below the ground surface. 45 Detroit's climate follows a four-season pattern, with average temperatures ranging from −7.11 °C to 28.7 °C. Detroit averages 87 cm and 137 days of precipitation per year.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Teimoori et al (2021) found that the modeled depth to groundwater in Detroit ranged from approximately 1-3 meters below the ground surface. 45 Detroit's climate follows a four-season pattern, with average temperatures ranging from −7.11 °C to 28.7 °C. Detroit averages 87 cm and 137 days of precipitation per year.…”
Section: Case Studymentioning
confidence: 99%
“…This illustrates the importance of evaluating groundwater levels when planning urban GI installations, especially since many urban areas have shallow groundwater tables, 61 including Detroit. 45 The correlation with longitude may be explained by prolonged soil compaction from development in central Detroit. 62 Some physiographic features had low correlation with the decay constants.…”
Section: Gi Drawdown Dynamicsmentioning
confidence: 99%
“…The main directions of the current research worldwide in urban hydrogeology are well balanced in this Special Issue. Three papers [3][4][5] describe different research experiences in quantitative urban groundwater studies with case studies in Detroit, USA, and Nantes, France, the third one being a laboratory study. The qualitative urban groundwater nucleus of this volume is represented by three other papers of three distinct cases studies that describe distinct groundwater contamination problems.…”
Section: Summary Of This Special Issuementioning
confidence: 99%
“…A study [3] in the Great Lakes Basin in Detroit, USA, provides an improved understanding of urban groundwater focusing on two approaches: the regional and local areas. A regional groundwater model that encompasses four major watersheds has been defined to outline the large-scale groundwater characteristics.…”
Section: Summary Of This Special Issuementioning
confidence: 99%
“…Anthropogenic modifications to urban groundwater systems-urban areas are zones of high anthropogenic disturbance that alter the natural water cycle. Urban water cycles require new and diverse strategies to adequately manage groundwater depth, flow, and quality [90,91].…”
Section: Key Challengesmentioning
confidence: 99%